The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s43152-021-00030-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Remodeling in Chronic Liver Disease

Abstract: Purpose of the Review This review aims to summarize the current knowledge of the extracellular matrix remodeling during hepatic fibrosis. We discuss the diverse interactions of the extracellular matrix with hepatic cells and the surrounding matrix in liver fibrosis, with the focus on the molecular pathways and the mechanisms that regulate extracellular matrix remodeling. Recent Findings The extracellular matrix not only provides structure and support for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 185 publications
0
29
0
Order By: Relevance
“…The altered ECM landscape in liver cirrhosis include the upregulation of collagens (type I, III, IV, V, VI, VIII, X, XI, XII, XIV, XV, XVI, XVIII, XXI), proteoglycans such as versican, decorin, lumican, and glycoproteins including fibulins, fibronectin, and laminins (Dataset EV5 ). Type X and XI collagens (COL10A1 and COL11A2) are the highest up‐regulated collagens, even though type I collagen (COL1A1, COL1A2) is the most abundant protein in the ECM, suggesting that not only the overall abundance but also the quantitative composition of the ECM constituents is altered in cirrhotic liver (Praktiknjo et al , 2018 ; Ortiz et al , 2021 ). To investigate this in a quantitative manner, we extracted all significantly elevated ECM associated proteins in cirrhotic liver and plotted their abundance rank in cirrhotic and healthy liver respectively which revealed 20 proteins whose abundance rank shifted by at least 20 (Fig 7F ).…”
Section: Resultsmentioning
confidence: 99%
“…The altered ECM landscape in liver cirrhosis include the upregulation of collagens (type I, III, IV, V, VI, VIII, X, XI, XII, XIV, XV, XVI, XVIII, XXI), proteoglycans such as versican, decorin, lumican, and glycoproteins including fibulins, fibronectin, and laminins (Dataset EV5 ). Type X and XI collagens (COL10A1 and COL11A2) are the highest up‐regulated collagens, even though type I collagen (COL1A1, COL1A2) is the most abundant protein in the ECM, suggesting that not only the overall abundance but also the quantitative composition of the ECM constituents is altered in cirrhotic liver (Praktiknjo et al , 2018 ; Ortiz et al , 2021 ). To investigate this in a quantitative manner, we extracted all significantly elevated ECM associated proteins in cirrhotic liver and plotted their abundance rank in cirrhotic and healthy liver respectively which revealed 20 proteins whose abundance rank shifted by at least 20 (Fig 7F ).…”
Section: Resultsmentioning
confidence: 99%
“…Further pointing to a protective action of OEA, we found that IL6 protein levels (Fig. 3e) and transcription of genes involved in liver inflammation and fibrosis – including C-C motif chemokine ligand 2 ( Ccl2 ) [26], interleukin 1β ( Il1b ) [27], and collagen type I α1 ( Col1a1 ) [28] – were attenuated in OEA-treated mice relative to controls (Fig. 3f–h), whereas transcription of the protective factor heme oxygenase 1 ( Hmox1 ) was enhanced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The altered ECM landscape in liver cirrhosis include the upregulation of collagens (type I, III, IV, V, VI, VIII, X, XI, XII, XIV, XV, XVI, XVIII, XXI), proteoglycans such as versican, decorin, lumican, and glycoproteins including fibulins, fibronectin and laminins (Dataset EV5). Type X and XI collagens (COL10A1 and COL11A2) are the highest up-regulated collagens, even though type I collagen (COL1A1, COL1A2) is the most abundant protein in the ECM, suggesting that not only the overall abundance but also the quantitative composition of the ECM constituents is altered in cirrhotic liver (Ortiz et al , 2021; Praktiknjo et al , 2018). To investigate this in a quantitative manner, we extracted all significantly elevated ECM associated proteins in cirrhotic liver and plotted their abundance rank in cirrhotic and healthy liver respectively which revealed 20 proteins whose abundance rank shifted by at least 20 (Fig 7f).…”
Section: Resultsmentioning
confidence: 99%